Characterization by soft ionization mass spectrometry methods of mono- and oligosaccharides functionalized at the anomeric center - Bozin Loreta-Andrea (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
In order to obtain oligosaccharides functionalized with amine groups, aliphatic diamines and polyamines were coupled with maltose by using reductive amination reactions. The synthesized compounds were characterized through electrospray ionization mass spectrometry (ESI-MS), while finer structural details were obtained by using MS.